Does the Norwegian Police Force Need a Well-Functioning Combat Mindset? - Boe, Ole; Torgersen, Glenn-Egil; Skoglund, Tom Hilding (Frontiers in Psychology, 2020)
This article discusses the apparent lack of a well-functioning combat mindset evident in the Norwegian Police Force during the terrorist attacks in Norway on 22 July, 2011. We describe what a well-functioning combat mindset is, and then continue to discuss major challenges linked to the current mindset in the Norwegian Police Force. We then elaborate upon how the experience of a stress reaction may affect one's ability to solve a mission. Then we describe how to cope with stress and the importance of an well-functioning combat mindset, and discuss techniques in order to build a well-functioning combat mindset. Furthermore, we describe how an extreme cognitive load and a well-functioning combat mindset are related. Finally, we suggest a method for practicing combat mindset (CM-training). The combat mindset training needs to include both realistic training and systematic reflection if one wants a better ability to deal with sudden and unforeseen events.